White Matter Perivascular Spaces on Magnetic Resonance Imaging: Marker of Cerebrovascular Amyloid Burden? - Charidimou, Andreas; Hong, Young T.; Jäger, Hans R.; Fox, Zoe; Aigbirhio, Franklin I.; Fryer, Tim D.; Menon, David K.; Warburton, Elizabeth A.; Werring, David J.; Baron, Jean-Claude (Stroke (1970), 2015)
BACKGROUND AND PURPOSE—We investigated the relationship between magnetic resonance imaging-visible centrum semiovale perivascular spaces (CSO-PVS), a biomarker of impaired interstitial fluid drainage, and positron emission tomography–based amyloid-β burden across a wide range of cerebrovascular amyloid deposition. METHODS—Thirty-one nondemented subjects (11 probable cerebral amyloid angiopathy patients and 10 healthy subjects ≥60 years; 10 older individuals, <60 years) had brain magnetic resonance imaging and Pittsburgh compound B-positron emission tomography. CSO-PVS was evaluated on T2-magnetic resonance imaging using a 4-point scale. The association between Pittsburgh compound B and CSO-PVS was assessed in linear regression. RESULTS—In multivariable analyses adjusted for age, microbleeds and white matter hyperintensities, whole cortex Pittsburgh compound B binding was associated with CSO-PVS degree both as continuous (coefficient, 0.11; 95% confidence interval, 0.01–0.22; P=0.040) and as dichotomous variable (coefficient, 0.27; 95% confidence interval, 0.11–0.44; P=0.002). The median Pittsburgh compound B retention was higher in high versus low CSO-PVS degree (P=0.0007). CONCLUSIONS—This pilot study suggests a possible association between cerebrovascular amyloid deposition and CSO-PVS, with potential pathophysiological implications.